2015
DOI: 10.5380/rf.v45i3.34441
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Operacional De Uma Serraria De Pequeno Porte Do Município De Alegre, Espírito Santo, Brasil

Abstract: ResumoAs serrarias são as principais indústrias madeireiras do sul do estado do Espírito Santo. O objetivo deste trabalho foi analisar o desempenho operacional de uma serraria de pequeno porte processadora da madeira de Eucalyptus sp. no município de Alegre, região sul do estado do Espírito Santo. Para tanto, a análise consistiu do estudo do rendimento em madeira serrada, eficiência operacional e amostragem do trabalho. O rendimento médio foi igual a 53,6% e foi considerado bom, para uma serraria que processa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
3
1
2
Order By: Relevance
“…In a study made by Batista et al (2015) on operational performance in a small sawmill, it was observed an averaged operating efficiency of 2.77 m³/worker/day, a higher result than the average value found in this present study (0.85 m³/worker/day). Marchesan et al (2014), in a study on technical efficiency in sawing logs of three main tropical species, found average values between 2.25 and 2.63m³/worker/day, superior in relation to the findings in this study.…”
Section: Yield In Lumber and Operational Efficiencycontrasting
confidence: 88%
“…In a study made by Batista et al (2015) on operational performance in a small sawmill, it was observed an averaged operating efficiency of 2.77 m³/worker/day, a higher result than the average value found in this present study (0.85 m³/worker/day). Marchesan et al (2014), in a study on technical efficiency in sawing logs of three main tropical species, found average values between 2.25 and 2.63m³/worker/day, superior in relation to the findings in this study.…”
Section: Yield In Lumber and Operational Efficiencycontrasting
confidence: 88%
“…Desse modo, a conicidade não foi um fator significativo no rendimento médio obtido neste trabalho. Batista et al (2015) afirmam que os fatores que influenciam no rendimento em madeira serrada vão além das características da madeira e da qualidade de toras, pois incluem mão de obra, maquinário utilizado, nível de automação, sistema de desdobro, modelos de corte e produto (dimensões das peças serradas).…”
Section: Resultsunclassified
“…Of the industries visited, 11 use residues generated in the industry itself and a sawmill industry disposes of the total residues generated for sale. In general, in the wood industries, due to the technology used, combined with the use of outdated equipment, there is low use of the raw material wood (BATISTA et al, 2015).…”
Section: Assessment Of Solid Residues Management and Environmental Pe...mentioning
confidence: 99%